Potential of Natural Products of Herbal Origin as Monoamine Oxidase Inhibitors - Erdogan Orhan, Ilkay (Current Pharmaceutical Design, 2016)
Monoamine oxidase (MAO, E.C. 1.4.3.4) is a flavin-adenine type of enzyme with two isoforms referred to MAO-A and MAO-B that function for oxidation of monoamines. While MAO-A inhibitors are effective as antidepressant and anxiolytic drugs (e.g. chlorgyline, moclobemide, and lazabemide), inhibitors of MAO-B (e.g. Ldeprenyl, pargyline, and rasagiline) are used against neurodegenerative diseases such as Parkinson’s and Alzheimer’s diseases. Considering the need for novel MAO inhibitors due to side effects of the current ones, natural products have become attractive targets for researchers. Up till now, many studies revealed strong MAO inhibitory activity of flavonoid, xanthone, alkaloid, and coumarin derivatives from herbal sources, which also become good models for the synthetic MAO inhibitors. For this purpose, the present review focuses on examples of in vitro and in vivo MAO-inhibiting natural compounds of plant origin from a wide variety of chemical classes isolated mainly between 2000 – 2015.
Keywords: coumarin